Development and Accuracy Test of a Fused Deposition Modeling (FDM) 3D Printing using H-Bot Mechanism - Budi Hadisujoto; Robby Wijaya (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2021)
Additive manufacturing process known as the 3D printing process is an advanced manufacturing process including one of the components to support industrial revolution 4.0. The initial development of a 3D printing machine at Sampoerna University is the background of this research. The 3D printing setup of Fused Deposition Modeling (FDM) was built using H-bot moving mechanism by considering the rigidity aspect. The FDM printing method is selected due to its cost and reliability. In this early development, the brackets were custom made using a 3D printer with Polylactic Acid (PLA) material. The result showed that the software worked properly in accordance with the assembled mechanical and electrical parts. The 3D printer could print simple objects such as planes and cubes with small dimensions. However, the printing specimen still lacked accuracy caused by the less rigidity of linear rail brackets, less coplanar belt arrangement, and error in some electronic components.